Corporate Governance and Sustainability Reporting: Implications for Firm Performance - Nuryadi Nuryadi; Nurna Aziza (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine how corporate governance mechanisms (Board of Directors’ expertise and size, and Audit Committee expertise and size) along with sustainability reporting practices, affect the financial performance of food and beverage companies listed on the Indonesia Stock Exchange during 2021–2023. Methodology/approach: Using purposive sampling, we selected F&B firms that published comprehensive financial and sustainability reports over the three-year period. Secondary data were collected from the Indonesia Stock Exchange website (www.idx.co.id) and analyzed with multiple linear regression in IBM SPSS Statistics 27. Results/findings: Board expertise showed a significant negative effect on both ROA and ROE, while board size had no significant impact. Audit committee expertise did not influence either performance measure, but audit committee size had a significant positive effect on both ROA and ROE. Sustainability reporting practice was not significantly related to firm performance. Conlcusion: These findings confirm that the effectiveness of governance and sustainability reporting heavily depends on the quality of implementation and regulatory context, not just formal compliance. The implication is that companies need to prioritize the effectiveness and independence of the board, while regulators are encouraged to develop more substantive sustainability disclosure standards. Limitations: The study is limited to food and beverage companies that publish complete financial and sustainability data, which may restrict the generalizability of the results to other sectors or firms with less transparency. Contribution: By highlighting the differing impacts of governance characteristics on firm performance, this research informs corporate governance policy and practice in the F&B industry. It offers guidance to regulators, board members, and investors on optimizing board and committee structures to enhance financial performance.